Carbon Tax Implementation In Malaysia: Public Acceptance And Trust In The Government - Norfakhirah Nazihah binti Mohd Hasnu
Carbon emissions in the atmosphere have become a major global concern. Many developed countries in Europe (examples: Finland, Poland, Norway, Sweden, Denmark) have adopted the carbon tax policy for decades. Meanwhile, among developing countries, only several countries (example: Chile, Mexico, Ukraine, Argentina) have adopted the carbon tax policy for years. Experiences from developed and developing countries proved that carbon tax is one of the best ways to reduce carbon dioxide (CO2) emissions and improve economic growth. In Malaysia, the implementation of a carbon tax has been identified as a target for future environmental sustainability development as part of the strategic development of the 12th Malaysia Plan (12MP), as indicated in the Economic Planning Unit 2019. To successfully implement a carbon tax, having public support for the carbon tax is crucial to avoid public resistance to its implementation. However, trust in the government is a major problem faced by many developing countries. In addition, limited studies on public acceptance of carbon tax had been conducted in the context of developing countries. Malaysia has experienced an increase in trust issues as a result of the government change in early 2018. This has had a negative influence on the Malaysian government, with the public losing trust in the government in comparison to other organisations. These have prompted concerns about public support for the proposed carbon tax. Thus, this study intends to conduct a study on the pre-implementation of carbon tax using the trust theory by examining how trust in the government influences public acceptance of the carbon tax implementation in Malaysia. The variables tested in the study are political trust, government’s integrity, government’s competence, and government’s accountability. This study adopts the quantitative research methodology to achieve the research objectives by distributing an online questionnaire to Malaysian citizens, and 566 respondents completed the survey. The data of the study was analyzed using the Statistical Package for Social Science (SPSS). The result of the study indicated that the government’s competence and accountability are the factors that influence public acceptance of the carbon tax. The other factors (political trust and government’s integrity) have no significant influence on the public acceptance of carbon tax. This study contribute to the extension of literature on trust towards the government and carbon tax as well as enhance the knowledge of policymakers in implementing the carbon tax policy in Malaysia. Examining the public acceptance on carbon tax will help the government to take earlier precaution to avoid public opposition against carbon tax.